Analisis Manajemen Risiko Finansial Terhadap Pom Coffee Room pada Saat Resesi Tahun 2023 - Fikra Terisha Azzikra; Melvin Melvin; Owen Owen; Putri Sahara; Rynando Sadrakh Halim (Yayasan Literasi Sains Indonesia, 2023)
This research was conducted with the aim of analyzing the financial risk of the POM Coffee Room during the 2023 recession. The POM Coffee Room is an MSME that sells coffee drinks as its main product. Its presence is able to encourage economic growth in Indonesia. In the world of business or business, of course there are risks caused by an uncertainty that will result in losses for a company. Even though there are many risks that will arise in a business, these risks can be watched out for and handled with risk management. In this study, researchers used qualitative research methods with the approach used by observing and interviewing partners. The author conducted an analysis on a small business, namely POM Coffee Room regarding the risks that will be faced if a recession occurs in 2023. The results obtained are that if a recession in 2023 does occur, then there are several risks that might occur to the cafe. The author also determines the level of probability and severity of risk in order to minimize the risks that will occur.